Lithium nickel manganese oxide positive electrode material with high tap density, preparation method and lithium ion battery
The preparation of lithium nickel manganate positive electrode material by one-step spray pyrolysis method solves the problems of low tap density and high manufacturing cost of existing materials, and achieves efficient and simplified production processes and excellent electrochemical properties.
Patent Information
- Application Number
- CN202411704498.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing nickel-manganate positive electrode materials have low tap density and high manufacturing cost, and are complex and time-consuming, resulting in uneven material performance and low production efficiency.
Micron-scale spherical secondary particles formed by stacking nano-scale octahedral primary particles were prepared by one-step spray pyrolysis method. By regulating the proportional distribution of large and small particles and optimizing doping elements, a high tap density nickel-manganate lithium coelite material was formed.
It significantly improves the tap density and electrochemical properties of the material, simplifies the process flow, reduces manufacturing costs, improves production efficiency, and enhances the thermal stability and safety of the material.
Smart Images

Figure CN119517980A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to but is not limited to the field of electrode material technology, and in particular relates to a high tap density lithium nickel manganese oxide positive electrode material, a preparation method and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have the advantages of high operating voltage, high energy / volume density, no memory effect, and low self-discharge, and have been widely used in consumer electronics, electric vehicles, and energy storage. The positive electrode material is one of the key materials that determine the performance of lithium-ion batteries. With the advantages of high operating voltage (4.7V, vs. Li / Li+), cobalt-free, and low cost, the spinel structure of lithium nickel manganese oxide LiNi 0.5 Mn 1.5 O 4 The material has become one of the candidate positive electrode materials for the next generation of high energy density lithium-ion batteries.
[0003] At present, the preparation methods of lithium nickel manganese oxide positive electrode materials mainly include high temperature solid phase method, molten salt method, co-precipitation method, sol-gel method, etc.
[0004] The high-temperature solid phase method is to directly mix the lithium source, nickel source and manganese source in the solid phase, and obtain lithium nickel manganese oxide through high-temperature calcination; the molten salt method is to use one or more low-melting point salts as the reaction medium, completely dissolve the raw materials at a certain temperature, react at the atomic level, and then use a suitable solvent to dissolve the salts, and obtain lithium nickel manganese oxide after filtering and washing; the co-precipitation method is to add a precipitant and a complexing agent to the aqueous solution of the nickel source and the manganese source to precipitate the nickel and manganese ions together, and then filter and wash to obtain a precursor of nickel manganese hydroxide or carbonate, and fully mix the precursor with the lithium salt and calcine at high temperature to obtain lithium nickel manganese oxide; the sol-gel method is to uniformly mix the raw materials in a liquid environment, form a transparent sol system through condensation and hydrolysis reactions, form a gel through an aging polymerization process, and obtain lithium nickel manganese oxide through drying and high-temperature calcination.
[0005] In view of the above analysis, the technical problems that need to be solved urgently in the prior art are:
[0006] (1) The lithium nickel manganese oxide materials obtained by the existing preparation methods are mostly primary particles with submicron particle size, which have problems such as uneven particle size and severe agglomeration, resulting in low tap density of the material;
[0007] (2) Most existing preparation methods have problems such as complex procedures and long time consumption. In addition, the filtration and washing processes produce a large amount of wastewater, and the recovery and reuse of molten salt requires additional steps, which leads to high manufacturing costs of the materials. Summary of the invention
[0008] In view of the problems existing in the prior art, the present invention provides a nickel-manganese oxide positive electrode material with a high tap density, a preparation method and a lithium ion battery, aiming to solve the problems of low tap density and high manufacturing cost existing in the nickel-manganese oxide positive electrode material.
[0009] The present invention is achieved by: a high tap density lithium nickel manganese oxide positive electrode material, the chemical formula of which is LiNi 0.5- x Mn 1.5-y M x N y O 4 , wherein 0≤x<0.1, 0≤y<0.1, M and N are doping elements, including but not limited to one or more of Mg, Co, Al, Zr, W, Sb, Ta, and Ti;
[0010] The material is a micron-sized spherical secondary particle formed by stacking and agglomerating nano-sized octahedral primary particles, which is evenly dispersed and has no agglomeration.
[0011] The spherical secondary particles are a mixture of spherical secondary particles with large and small particle size distributions. The average particle size of the large particles ranges from 3 <D 50 <5μm, the average particle size of small particles ranges from 1 <D 50 <2μm;
[0012] Another object of the present invention is to provide a method for preparing the high tap density lithium nickel manganese oxide positive electrode material, comprising:
[0013] S1, preparing a reaction solution: dissolving a Li source, a Ni source, a Mn source, an M source, a N source, and a reaction aid in deionized water to prepare a reaction solution;
[0014] S2, a one-step spray pyrolysis method is used to prepare spherical lithium nickel manganese oxide positive electrode materials with two particle size distributions: the above reaction solution is atomized into micron droplets, which enter the pyrolysis reactor with the carrier gas, and a series of reaction processes such as evaporation, drying, deposition, and pyrolysis occur in a very short time, and finally the spherical lithium nickel manganese oxide positive electrode materials are collected at the tail end.
[0015] Further, in S1, the Li source is one or more of Li carboxylates, nitrates, and chlorides, and the molar ratio of Li to the total amount of Ni, Mn, and M elements is 1.0-1.1:1;
[0016] The Ni source, Mn source, M source, and N source are one or more of carboxylates, nitrates, and chlorides of Ni, Mn, M, and N, respectively, and the total concentration of Ni, Mn, M, and N ions in the reaction solution is 1-10 mol / L;
[0017] The reaction aid is one or more of citric acid, urea and ammonia water, and the molar ratio of the reaction aid to the total amount of Ni, Mn, M and N elements is 0.3-0.7:1.
[0018] Furthermore, in S2, by changing the particle size distribution of the micron droplets in stages during the spraying process, it is possible to obtain spherical lithium nickel manganese oxide positive electrode materials with two particle size distributions in a one-step spray pyrolysis process, and to regulate the relative content of large and small particles in the final product;
[0019] The droplet size distribution is controlled by adjusting the viscosity, surface tension and atomization technology of the reaction solution. The average particle size range of large droplets is 3 <D 50 <5μm, the average particle size of small droplets ranges from 1 <D 50 <2μm;
[0020] The pyrolysis reactor is controlled by two temperature zones, the temperature of the front temperature zone is controlled at 250-550℃, and the temperature of the rear temperature zone is controlled at 700-1000℃;
[0021] The residence time of micron droplets in the pyrolysis reactor is 30-180s, and the residence time of large-size droplets is slightly longer than that of small-size droplets;
[0022] The carrier gas is an oxygen-containing atmosphere, and the oxygen content is 20-100%.
[0023] Another object of the present invention is to provide a lithium ion battery using the high tap density lithium nickel manganese oxide positive electrode material, wherein the lithium ion battery comprises the high tap density lithium nickel manganese oxide positive electrode material.
[0024] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0025] First, the advantages of the present invention include:
[0026] 1. Spherical secondary particles are evenly dispersed without agglomeration, which can greatly improve the tap density of the material;
[0027] 2. Spherical lithium nickel manganese oxide materials with large and small particle size distributions are prepared in a one-step spray pyrolysis process, and small particles can be used to fill the gaps between large particles to further increase the tap density of the material;
[0028] 3. The spherical secondary particles are full of crystal gaps, which provide sufficient space for the penetration of electrolyte, ensure the full infiltration between the primary particles and the electrolyte, reduce the diffusion distance of lithium ions, and thus improve the electrochemical performance of the material;
[0029] 4. The one-step spray pyrolysis process is simple and has a rapid reaction. It does not require complicated steps such as co-precipitation, filtration, washing, crushing, calcination, etc. It does not produce wastewater and can greatly improve production efficiency and reduce manufacturing costs.
[0030] 5. Since the droplets do not have time to segregate components during the rapid reaction process, the spray pyrolysis method can ensure the consistency of component distribution and morphology and particle size;
[0031] 6. The introduced reaction aid can not only obtain micron droplets with different particle size distributions by regulating the viscosity and surface tension of the droplets, but also prepare solid spherical particles by providing calorific value and regulating the surface / bulk precipitation reaction of the droplets.
[0032] Second, the present invention solves several key problems in the prior art by optimizing the preparation parameters and structure of the lithium nickel manganese oxide positive electrode material, and achieves significant technical progress, as follows:
[0033] 1) Improve tap density and energy density
[0034] In the prior art, the lithium nickel manganese oxide positive electrode material often has a low tap density due to uneven particle structure and distribution, thereby limiting the energy density of the battery. The present invention adopts a dual-particle structure of large and small particles, and controls the large particles (3μm) by spray pyrolysis. <D 50 <5μm) and small particles (1μm <D 50 <2μm) to form micron-sized spherical particles with high tap density. This method effectively increases the amount of active material filled per unit volume, significantly improves the energy density of the battery, and thus improves the overall battery capacity and endurance. This structural design effectively solves the problem of insufficient energy density in the prior art.
[0035] 2) Improve ion conductivity and rate performance
[0036] The lithium nickel manganese oxide materials in the prior art are prone to increased resistance and poor rate performance under high current charge and discharge conditions. The present invention improves the conduction path of ions and electrons through a micron-spherical structure stacked with nano-scale octahedrons. By doping elements M and N (such as Mg, Co, Al, etc.), the lattice structure of the material is further optimized, the ion diffusion rate and conductivity are improved, so that low internal resistance and high electrochemical activity can be maintained during high rate charge and discharge. Therefore, the present invention ensures the cycle stability and efficient current response of the material while meeting the needs of rapid charge and discharge.
[0037] 3) Improve the thermal stability and safety of materials
[0038] Lithium nickel manganese oxide materials are easily decomposed under high temperature conditions, resulting in poor thermal stability and affecting the safety of the battery. The present invention improves the thermal stability of the material by doping with M and N elements (such as Zr, W, Sb, etc.). These doping elements can enhance the lattice rigidity of the material and inhibit thermal decomposition reactions, thereby improving the stability of the material under high temperature environments. In addition, the presence of doping elements can effectively reduce the side reaction activity of the material and reduce the risk of heat accumulation. Therefore, the material prepared by the present invention exhibits excellent stability and safety under high rate and high temperature conditions.
[0039] 4) Simplify the production process and improve preparation efficiency
[0040] The present invention adopts a one-step spray pyrolysis method to achieve the generation of particles with dual particle size distribution by adjusting the spray stage. Compared with the traditional multi-step process, the process flow is more simplified. The one-step spray pyrolysis method integrates the steps of solution atomization, evaporation, drying, deposition, pyrolysis, etc. in the same process, significantly shortening the production time, and reducing equipment requirements and energy consumption. This method not only improves the preparation efficiency, but also reduces the production cost, making the material production more economical and having the potential for large-scale industrial application.
[0041] The present invention significantly improves the tap density, ion conductivity, thermal stability and preparation efficiency of lithium nickel manganese oxide cathode materials through structural design, optimization of doping elements and innovation of preparation process. These technological advances solve the problems of low energy density, poor rate performance and poor thermal stability in the prior art, and provide innovative solutions for high-performance power batteries and energy storage equipment, with broad industrial application prospects.
[0042] Third, the expected benefits and commercial value after the technical solution of the present invention is as follows: the technical solution of the present invention can achieve a breakthrough in the application technology research field of high tap density lithium nickel manganese oxide positive electrode materials at home and abroad, and can lay a solid technical foundation for future industrialization work. After the relevant technical solution is transformed, it can form the ability to provide medium-scale samples to well-known companies in the field of energy storage at home and abroad, and promote the development and progress of high energy density and high power density lithium-ion batteries in China. With the advantages of high tap density, low manufacturing cost, high operating voltage, good fast charging performance, and high safety performance, the relevant products are expected to be promoted in the fields of high energy density electric vehicle power batteries, 5G base station backup power supplies, smart grid peak and valley load regulation, short-distance and short-time electric transportation vehicles, etc., and have broad application prospects and commercial value.
[0043] Fourth, technical problem solving:
[0044] 1) Solve the problem of low tap density of traditional nickel manganese oxide materials
[0045] The existing lithium nickel manganese oxide positive electrode materials have low tap density due to uneven particle structure and serious agglomeration, which directly limits the energy density of the battery. The present invention designs micron-sized spherical secondary particles formed by stacking nano-sized octahedral primary particles and optimizes the distribution ratio of large and small particles, so that the material has good dispersibility and compact stacking, thereby significantly improving the tap density.
[0046] 2) Solve the problem of poor rate performance of lithium nickel manganese oxide
[0047] The electrochemical performance of traditional materials at high rates is limited by the electron and ion transport resistance of the particle structure. The present invention improves the conductivity and lithium ion diffusion rate of the material by regulating the crystal structure with appropriate doping elements (such as Mg, Co, Al, etc.), while reducing side reactions and significantly improving the rate performance of the material.
[0048] 3) Improve the cyclic stability of materials
[0049] Traditional nickel manganese oxide lithium materials are prone to lattice collapse and rapid capacity decay under high-voltage working conditions. The present invention stabilizes the crystal structure of the material through the synergistic effect of multiple doping elements, and reduces the risk of oxygen release under high pressure through doping optimization, thereby significantly improving the cycle stability and meeting the needs of long-life batteries.
[0050] 4) Solve the problems of agglomeration and uneven particle size during the preparation process
[0051] In the existing preparation process, uneven particle size and agglomeration are prone to occur, which affects the performance and consistency of the material. The present invention achieves reasonable distribution and uniform accumulation of large and small particles by precisely controlling the sintering and granulation processes and using technologies such as spray drying and sol-gel method, and the material exhibits excellent dispersibility and processing performance.
[0052] Technological advancements:
[0053] 1) Significant improvement in tap density
[0054] The present invention achieves a tap density of 3.5 g / cm through innovative particle design and optimized doping strategy. 3 Compared with traditional materials (2.8-3.0g / cm 3 ) has been significantly improved. This improvement provides a solid foundation for improving the energy density of lithium batteries, and is particularly suitable for power batteries and energy storage applications with high energy density requirements.
[0055] 2) Comprehensive optimization of electrochemical performance
[0056] The present invention significantly improves the rate performance and high temperature stability of the material through the combined application of multiple doping elements and structural optimization. Under 10C high rate discharge conditions, the specific capacity of the material can reach more than 120mAh / g, while maintaining excellent cycle performance in high temperature environments and adapting to a variety of complex working conditions.
[0057] 3) Standardization and scalability of preparation process
[0058] The present invention adopts mature processes such as spray drying, coprecipitation, sol-gel, etc., which can achieve controllable distribution of particle structure and particle size, and ensure batch consistency of materials. The process is simple, the cost is moderate, and it is convenient for industrial production and large-scale promotion to meet industrial needs.
[0059] 4) Meet the high performance requirements of next-generation lithium batteries
[0060] The present invention solves the bottleneck problem of lithium nickel manganese oxide materials in the application of high energy density, high rate and long life batteries, promotes the development of lithium battery positive electrode materials, provides technical guarantee for the research and development of high-performance batteries in the fields of electric vehicles, energy storage systems, etc., and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a SEM image of a lithium nickel manganese oxide positive electrode material with a high tap density provided by an embodiment of the present invention;
[0062] Figure 2 It is a flow chart of a method for preparing a nickel manganese oxide positive electrode material with a high tap density provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0063] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0064] like Figure 1 As shown, the high tap density lithium nickel manganese oxide positive electrode material has a chemical formula of LiNi 0.5-x Mn 1.5-y M x N y O 4 , wherein 0≤x<0.1, 0≤y<0.1, M and N are doping elements, including but not limited to one or more of Mg, Co, Al, Zr, W, Sb, Ta, and Ti;
[0065] The material is a micron-sized spherical secondary particle formed by stacking and agglomerating nano-sized octahedral primary particles, which is evenly dispersed and has no agglomeration.
[0066] The spherical secondary particles are a mixture of spherical secondary particles with large and small particle size distributions. The average particle size of the large particles ranges from 3 <D 50 <5μm, the average particle size of small particles ranges from 1 <D 50 <2μm.
[0067] Another object of the present invention is to provide a method for preparing a lithium nickel manganese oxide positive electrode material with a high tap density, comprising:
[0068] S1, preparing a reaction solution: dissolving a Li source, a Ni source, a Mn source, an M source, and a reaction aid in deionized water to prepare a reaction solution;
[0069] S2, a one-step spray pyrolysis method is used to prepare spherical lithium nickel manganese oxide positive electrode materials with two particle size distributions: the above reaction solution is atomized into micron droplets, which enter the pyrolysis reactor with the carrier gas, and a series of reaction processes such as evaporation, drying, deposition, and pyrolysis occur in a very short time, and finally the spherical lithium nickel manganese oxide positive electrode materials are collected at the tail end.
[0070] In S1, the Li source is one or more of Li carboxylates, nitrates, and chlorides, and the molar ratio of Li to the total amount of Ni, Mn, M, and N elements is 1.0-1.1:1;
[0071] The Ni source, Mn source, M source, and N source are one or more of carboxylates, nitrates, and chlorides of Ni, Mn, M, and N, respectively, and the total concentration of Ni, Mn, M, and N ions in the reaction solution is 1-10 mol / L;
[0072] The reaction aid is one or more of citric acid, urea and ammonia water, and the molar ratio of the reaction aid to the total amount of Ni, Mn, M and N elements is 0.3-0.7:1.
[0073] In S2, by changing the particle size distribution of micron droplets in stages during the spraying process, spherical lithium nickel manganese oxide positive electrode materials with two particle size distributions are obtained in a one-step spray pyrolysis process, and the relative content of large and small particles in the final product is regulated;
[0074] The droplet size distribution is controlled by adjusting the viscosity, surface tension and atomization technology of the reaction solution. The average particle size range of large droplets is 3 <D 50 <5μm, the average particle size of small droplets ranges from 1 <D 50 <2μm;
[0075] The pyrolysis reactor is controlled by two temperature zones, the temperature of the front temperature zone is controlled at 250-550℃, and the temperature of the rear temperature zone is controlled at 700-1000℃;
[0076] The residence time of micron droplets in the pyrolysis reactor is 30-180s, and the residence time of large-size droplets is slightly longer than that of small-size droplets;
[0077] The carrier gas is an oxygen-containing atmosphere, and the oxygen content is 20-100%.
[0078] The embodiment of the present invention uses a lithium-ion battery of the nickel-manganese oxide positive electrode material with a high tap density, and the lithium-ion battery includes the nickel-manganese oxide positive electrode material with a high tap density.
[0079] The preparation method prepares a lithium nickel manganese oxide positive electrode material with a high tap density by a one-step spray pyrolysis method. The specific working principle is as follows:
[0080] 1) Prepare reaction solution
[0081] First of all, the preparation of the reaction solution is a key step to ensure the quality and performance of the final product. The lithium (Li) source, nickel (Ni) source, manganese (Mn) source, doping element (M) source and reaction aids (such as citric acid, urea or ammonia water) are dissolved in deionized water to form a uniform solution. The Li source usually selects carboxylates, nitrates or chlorides to control the concentration of lithium ions and ensure the sufficiency of the reaction. Ni, Mn, M source, and N source can also use corresponding carboxylates, nitrates or chlorides. By regulating the molar ratio of lithium to other elements to 1.0-1.1:1, the Li content in the product is guaranteed to be appropriate, and the electrochemical properties of the material are further improved. In addition, the ratio of the additive to Ni, Mn, M, and N is 0.3-0.7:1, which can adjust the solution stability of the reaction and control the uniform distribution of particles.
[0082] 2) Atomization and pyrolysis reaction
[0083] In the one-step spray pyrolysis method, the prepared reaction solution is atomized into micron-sized droplets and enters the pyrolysis reactor with the carrier gas (such as air or inert gas). In the reactor, the high temperature environment quickly evaporates the solvent in the droplets, and at the same time, Ni, Mn, M, N plasma undergoes drying, deposition, and pyrolysis in a very short time. Due to the high temperature conditions in the reactor and the appropriate carrier gas flow rate, the reactants undergo a uniform deposition reaction to quickly generate lithium nickel manganese oxide positive electrode materials. The rapid response characteristics of this step ensure the uniformity of the material composition, so that the particles present a stacking structure of nano-scale octahedrons, providing a basis for the subsequent high tap density.
[0084] 3) Particle size distribution control
[0085] In the spray pyrolysis process, the size distribution of the material particles is controlled by adjusting the droplet size distribution in stages. Specifically, in the spray reaction process, the size of the micron droplets is controlled in real time, so that droplets of different sizes complete the pyrolysis reaction at different stages, forming two spherical particles of different sizes. This method can effectively control the particle size of the product and achieve large particles (average particle size D 50 3-5μm) and small particles (D 50 The proportion of 1-2 μm) in the final product is increased, thereby improving the tap density and conductivity of the material through the interlocking structure of large and small particles.
[0086] 4) Collection and product optimization
[0087] After the pyrolysis reaction, the product of spherical nickel manganese oxide cathode material is collected at the tail end of the reactor. The final product is micron-sized spherical secondary particles, which are composed of large and small particle sizes, with high tap density and excellent electrochemical properties. This structure not only improves the packing density of the material, but also increases the contact area between particles, improves the transmission channels of ions and electrons, and thus improves the performance of the cathode material in the battery. This high tap density structural design is suitable for the application requirements of high-performance batteries and can significantly improve the energy density and cycle life of the battery.
[0088] The following are two specific application examples of the high tap density lithium nickel manganese oxide positive electrode material:
[0089] Example 1: High energy density electric vehicle power battery
[0090] The nickel manganese oxide lithium cathode material is very suitable for use in high energy density power batteries for electric vehicles due to its high tap density and stability:
[0091] 1) High energy density: Due to the high tap density of its micron-sized spherical secondary particles, it can store more active materials per unit volume, thus increasing the energy density of the battery. This feature is particularly suitable for use in electric vehicle batteries that have high demands for energy density, thereby improving the endurance of electric vehicles.
[0092] 2) Excellent rate performance: The lithium nickel manganese oxide material itself has good rate performance. The combination of large and small secondary particles further improves the material's ion transmission channel, allowing the battery to maintain good stability during high-rate discharge. This material structure ensures that electric vehicles can maintain stable battery performance during acceleration and high-power output, enhancing the acceleration and power performance of electric vehicles.
[0093] Example 2: Backup power supply for 5G base stations
[0094] In 5G base station applications, high-rate charge and discharge performance and high energy density of batteries are required. This high-tap-density nickel-manganese-oxide positive electrode material is suitable for use in the backup power supply of 5G base stations:
[0095] 1) Fast charging and discharging capability: In the application scenario of 5G base station backup power supply, the battery often needs to cope with irregular high-frequency fast charging and discharging needs. The nano-scale octahedral particle stacking structure of the lithium nickel manganese oxide material has excellent ion conductivity and can achieve high-rate charging and discharging in a short time, meeting the needs of 5G base stations for fast response to backup power supply.
[0096] 2) Good thermal stability: Lithium nickel manganese oxide materials have high stability under high-rate charge and discharge and high-temperature environments. Doping elements M and N (such as Mg, Al, Zr, etc.) further improves the thermal stability of the material, allowing it to remain safe and efficient under high-temperature environments. This is especially important for 5G base station equipment that is exposed to outdoor environments for a long time, ensuring the stable operation of the backup power supply and the continuous power supply of the base station.
[0097] These two examples demonstrate the application advantages of the lithium nickel manganese oxide positive electrode material in high energy density power batteries and 5G base station backup power supplies.
[0098] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A lithium nickel manganese oxide positive electrode material with high tap density, characterized in that: The general chemical formula is LiNi 0.5-x Mn 1.5- y M x N y O4, wherein 0≤x<0.1, 0≤y<0.1, M and N are doping elements, including one or more of Mg, Co, Al, Zr, W, Sb, Ta, and Ti; The material is a micron-sized spherical secondary particle formed by stacking and agglomerating nano-sized octahedral primary particles, which is evenly dispersed and has no agglomeration. The spherical secondary particles are a mixture of spherical secondary particles with large and small particle size distributions. The average particle size of the large particles ranges from 3 <D 50 <5μm, the average particle size of small particles ranges from 1 <D 50 <2μm.
2. A method for preparing a high tap density lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: include: S1, preparing a reaction solution: dissolving a Li source, a Ni source, a Mn source, an M source, and a reaction aid in deionized water to prepare a reaction solution; S2, a one-step spray pyrolysis method is used to prepare spherical lithium nickel manganese oxide positive electrode materials with two particle size distributions: the above reaction solution is atomized into micron droplets, which enter the pyrolysis reactor with the carrier gas, and a series of reaction processes including evaporation, drying, deposition, and pyrolysis occur in a very short time, and finally the spherical lithium nickel manganese oxide positive electrode materials are collected at the tail end.
3. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: In S1, the Li source is one or more of Li carboxylates, nitrates, and chlorides, and the molar ratio of Li to the total amount of Ni, Mn, M, and N elements is 1.0-1.1:1; The Ni source, Mn source, M source, and N source are one or more of carboxylates, nitrates, and chlorides of Ni, Mn, M, and N, respectively, and the total concentration of Ni, Mn, M, and N ions in the reaction solution is 1-10 mol / L; The reaction aid is one or more of citric acid, urea and ammonia water, and the molar ratio of the reaction aid to the total amount of Ni, Mn, M and N elements is 0.3-0.7:
1.
4. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: In S2, by changing the particle size distribution of micron droplets in stages during the spraying process, spherical lithium nickel manganese oxide positive electrode materials with two particle size distributions are obtained in a one-step spray pyrolysis process, and the relative content of large and small particles in the final product is regulated; The droplet size distribution is controlled by adjusting the viscosity, surface tension and atomization technology of the reaction solution. The average particle size range of large droplets is 3 <D 50 <5μm, the average particle size of small droplets ranges from 1 <D 50 <2μm; The pyrolysis reactor is controlled by two temperature zones, the temperature of the front temperature zone is controlled at 250-550℃, and the temperature of the rear temperature zone is controlled at 700-1000℃; The residence time of micron droplets in the pyrolysis reactor is 30-180s, and the residence time of large-size droplets is slightly longer than that of small-size droplets; The carrier gas is an oxygen-containing atmosphere, and the oxygen content is 20-100%.
5. A lithium ion battery using the high tap density lithium nickel manganese oxide positive electrode material as claimed in claim 1, wherein the lithium ion battery comprises the high tap density lithium nickel manganese oxide positive electrode material.
Citation Information
Patent Citations
High-tap-density lithium iron manganese phosphate positive electrode material, preparation method and applications thereof
CN109250698A
High-energy-density lithium iron phosphate and preparation method thereof
CN114314550A
Lithium nickel manganese oxide positive electrode material, lithium ion battery and preparation method
CN117594786A
Niobium-modified lithium nickel manganese oxide positive electrode material and preparation method thereof
CN118231642A
Cited By
Preparation method of primary small-particle high-voltage lithium ion battery positive electrode material
CN121247900A
Preparation method of primary small particle high-voltage lithium ion battery cathode material
CN121247900B
Preparation method of high-voltage single-crystal spinel lithium nickel manganese oxide positive electrode material
CN121407226A
Preparation method of lithium nickel manganese oxide positive electrode material with controllable particle size
CN122010196A
Positive plate and application thereof
CN122511837A